Changes in the toxicity of procymidone and its metabolite during the photohydrolysis process and the effect of the presence of microplastics - Lee, Youn Jun; Yang, Ji Won; Choi, Byeongwook; Park, Seong Jik; Lee, Chang Gu; Jho, Eun Hea (Korean Journal of Chemical Engineering, 2023)
Procymidone (PCM), an agricultural fungicide, is attracting attention because it has been detected in all ecosystems, including aquatic environments. This study explored changes in the behavior and toxicity of PCM in water under the influence of photolysis and microplastics (MPs) coexistence. Hydrolysis of PCM was evaluated and UV-A and UV-C lamps were used as light sources for the photodegradation experiments. The Microtox® assay was used to evaluate changes in toxicity during the photodegradation and after sorption on MPs of low-density polyethylene (LDPE) and polyvinyl chloride (PVC) films. The appearance of 3,5-dichloroaniline (DCA), a major metabolite of PCM that is more toxic than its parent compound in water, was confirmed. Both PCM and DCA showed sufficient molar extinction coefficients to be photolyzed under UV-C irradiation (εPCM=10,300 M−1 cm−1 and εDCA=2,400 M−1 cm−1); however, the presence of natural organic matter negatively affected their photodegradation. PVC showed a better sorption potential for PCM and DCA than for LDPE. The higher sorption by PVC significantly reduced the toxic effect of DCA from an average value of 79% to 60% and increased the EC50 value from 30.4% to 47.6%. These results offer insights into controlling toxic micropollutants, including fungicides, in aquatic environments and water treatment processes.
Keywords: 3,5-Dichloroaniline; Microplastic Adsorption; Microtox®; Photolysis; Procymidone